Health and BigData: An Ethical Framework for Health Information Collection By Corporate Wellness Programs - Ajunwa, Ifeoma; Crawford, Kate; Ford, Joel (Law, Medicine and Ethics, 2016)
This essay details the resurgence of wellness program as employed by large corporations with the aim of reducing healthcare costs. The essay narrows in on a discussion of how big data collection practices are being utilized in wellness programs and the potential negative impact on the worker in regards to privacy and employment discrimination. The essay offers an ethical framework to be adopted by wellness program vendors in order to conduct wellness programs that would achieve cost-saving goals without undue burdens on the worker. The essay also offers some innovative approaches to wellness that may well better serve the goals of healthcare cost reduction.